An Overview On The Allelic Variant Of CYP2D6 Genotype - DR. SHIJU MATHEW (International Journal of Pharma and Bio Sciences, 2010)
The paper will give an overview on the allelic variant of CYP2D6 genotype. The gene CYP2D6*3 encodes a member of the cytochrome P450 superfamily of enzymes. The cytochrome P450 proteins are monooxygenases which catalyze many reactions involved in drug metabolism and synthesis of cholesterol, steroids and other lipids. The protein localizes to the endoplasmic reticulum and is known to metabolize as many as 20% of commonly prescribed drugs. Its substrates include debrisoquine, an adrenergic-blocking drug; sparteine and propafenone, both anti-arrythmic drugs; and amitryptiline, an anti-depressant. The emerging application of pharmacogenomics in the clinical trials requires careful comparison with the traditional genotypic methodologies particularly in the drug metabolism area.